Perlindungan Hukum Terhadap Kepemilikan Hak Atas Tanah Dalam Sistem Pertanahan di Indonesia Berdasarkan Perpres Nomor 36 Tahun 2005 Dan Perpres Nomor 65 Tahun 2006 Terhadap Pemilik Hak Atas Tanah Dalam Pengadaan Tanah Bagi Kepentingan Jalan Tol - Yanti Kirana; Riska Arianti (Res Justitia : Jurnal Ilmu Hukum, 2022)
The implementation of land acquisition, both related to land acquisition for development purposes for toll roads, as well as land acquisition for private interests, always causes problems, especially in terms of compensation, due to the unpreparedness of the apparatus. The research method used in this research is normative juridical using the approach of legal history, sociology of law, legal politics, and philosophy of law. The data used is secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Qualitative data analysis in this study is a description of positive law and systematization of positive law. The results of this study are that, the implementation of forms of compensation according to the Presidential Regulation of the Republic of Indonesia Number 99 of 2014 concerning the Implementation of Land Procurement for Development in the Public Interest, in Article 1 number 2 that compensation is appropriate and fair to the parties entitled to the land acquisition process. Compensation value is carried out per plot of land, including: land, aboveground and underground space, buildings, plants, objects related to land, and other losses that can be assessed in the form of: money, replacement land, resettlement, share ownership and other forms agreed by both parties. The mechanism for the amount of compensation, the entitled party can file an objection to the local District Court within a maximum of 14 working days after signing the minutes of the results of the deliberation